Flame-retardant aramid fabric with durable, self-cleaning, hydrophobic, and tunable electromagnetic interference shielding properties. (March 2023) - Wang, Bibo; Yin, Zhenting; Cheng, Wenhua; Zhang, Yan; Hu, Yuan
Abstract: Multifunctional textiles are urgently needed for harsh environments, such as fire hazards and strong electromagnetic fields. In this work, a functioned textile was prepared through the spraying-coating method, we introduced the magnetic Fe3 O4, conductive Ti3 C2 Tx, and protective polydimethylsiloxane (PDMS) to endow the modified aramid fabrics (AF) with excellent self-cleaning, super environment endurance and outstanding hydrophobic properties. Compared with the controlled samples, our results displayed that shielding effectiveness (SE) could achieve 40.78 dB, significantly meeting the needs of commercial appliances. High heat-resistance AF and metal compounds (Fe3 O4 and 2D Ti3 C2 Tx ) improved fire safety. A-T3Fe3-6 L can achieve self-extinguishing within 10 s. It also shows excellent anti-washable properties after 14 washes. The water contact angle of this system is maintained at 126.9°. Therefore, this work supplies a superb avenue for preparing multifunctional fabrics with high designability to be applied in diverse conditions.